The stubborn father - Brunstetter, Wanda E. (Brunstetter, Wanda E. Amish millionaire ;, 2016)
Widower Eustace Byler stands out in his Amish community for his eccentricity and his wealth. He mourns the loss of his son to the world like he mourns the physical loss of his wife. In the past, Eustace has freely loaned Joel money, perhaps hoping to entice him back home, but now Eustace is done and is moving on to fulfill some of his own dreams. Can father and son come to an understanding about their different choices in life before time runs out?